Residual enhancing disease after surgery for glioblastoma: evaluation of practice in the United Kingdom. Issue 2 (27th September 2017) - Ma, Ruichong; Chari, Aswin; Brennan, Paul M; Alalade, Andrew; Anderson, Ian; Solth, Anna; Marcus, Hani J; Watts, Colin; ,
Abstract: Background: A growing body of clinical data highlights the prognostic importance of achieving gross total resection (GTR) in patients with glioblastoma. The aim of this study was to determine nationwide practice and attitudes towards achieving GTR and dealing with residual enhancing disease. Methods: The study was in 2 parts: an electronic questionnaire sent to United Kingdom neuro-oncology surgeons to assess surgical practice followed by a 3-month prospective, multicenter observational study of current neurosurgical oncology practice. Results: Twenty-seven surgeons representing 22 neurosurgical units completed the questionnaire. Prospective data were collected for 113 patients from 15 neurosurgical units. GTR was deemed to be achieved at time of surgery in 82% (91/111) of cases, but in only 45% (36/80) on postoperative MRI. Residual enhancing disease was deemed operable in 16.3% (13/80) of cases, however, no patient underwent early repeat surgery for residual enhancing disease. The most commonly cited reason (38.5%, 5/13) was perceived lack of clinical benefit. Conclusion: There is a subset of patients for whom GTR is thought possible, but not achieved at surgery. For these patients, early repeat resection may improve overall survival. Further prospective surgical research is required to better define the prognostic implications of GTR for residual enhancing disease and examine the potential benefit of this early re-intervention.